Academic mobility: three cases of prospective pedagogues (Gumilyov Journal of Pedagogy, 2025)
Academic mobility is a powerful tool for prospective pedagogues seeking academic development, assisting young specialists in developing their pedagogical skills and abilities,immense professional experience, as well as in personal improvement and mentality expansion which are critical for their future careers. The paper examines three cases of prospective pedagogues and discusses the benefits and drawbacks they encountered during academic mobility in foreign countries. However, while conducting study, we discovered numerous challenges, both in terms of scheduling travel to a foreign country and in terms of complications encountered when the prospective pedagogue arrived. Consequently, the authors attempted to present the solutions to the problem by analyzing background and obtained data. Qualitative and quantitative methodologies were used, as well as a coding scheme for the gathered data; additionally, samples were selected at random on a voluntary basis. At the conclusion of the work, various implications and recommendations for future papers are offered.